1997
DOI: 10.1046/j.1365-2435.1997.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Light stress effects and antioxidative protection in two desert plants

Abstract: 1. The enzyme catalase was investigated as a sensitive marker of light stress in Retama raetam stems and Atriplex halimus leaves. While the activity of catalase was readily photoinactivated in vitro when crude extracts from these tissues were exposed to a photon flux of 500μmolm–2s–1 photosynthetic active radiation (PAR), no apparent losses of the extractable catalase activities were observed when tissues were harvested from desert plants at noon when light levels were as high as 2200μmolm–2s–1 PAR. 2. When s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Since it possesses the C 4 carboxylation pathway, the optimum temperature for photosynthesis is relatively high, around 35ºC (Shomer-Ilan et al, 1981;Le Houérou, 1992;Zervoudakis et al, 1998). Streb et al (1997), studying leaves of A. halimus plants exposed to photosynthetically active radiation in the field as high as 2200 µmol m -2 s -1 , found a limited capacity for the dissipation of light energy and for scavenging of ROS. They concluded that A. halimus is able to withstand high light intensity due to mutual shading of leaves and reflection of light from the leaf surface by a layer of salt crystals formed after the collapse of vesiculated hairs (Mozafar and Goodin, 1970), which gives the leaves a greenish-grey colour (Figure 1).…”
Section: Extreme Temperatures and Lightmentioning
confidence: 99%
“…Since it possesses the C 4 carboxylation pathway, the optimum temperature for photosynthesis is relatively high, around 35ºC (Shomer-Ilan et al, 1981;Le Houérou, 1992;Zervoudakis et al, 1998). Streb et al (1997), studying leaves of A. halimus plants exposed to photosynthetically active radiation in the field as high as 2200 µmol m -2 s -1 , found a limited capacity for the dissipation of light energy and for scavenging of ROS. They concluded that A. halimus is able to withstand high light intensity due to mutual shading of leaves and reflection of light from the leaf surface by a layer of salt crystals formed after the collapse of vesiculated hairs (Mozafar and Goodin, 1970), which gives the leaves a greenish-grey colour (Figure 1).…”
Section: Extreme Temperatures and Lightmentioning
confidence: 99%
“…During stress, increased H 2 O 2 production by elevated glycolate oxidase activity may further upset the balance between the production of reactive oxygen intermediates and the quenching activity of antioxidants if lipid peroxidation disrupts peroxisomal membrane integrity, causing leakage of H 2 O 2 into other compartments (Willekens et al 1997). In C 3 plants subjected to stress, endogenous catalase activity in the light may be inadequate for destruction of H 2 O 2 generated during photorespiration (Foyer, Lelandais & Kunert 1994;Streb, Tel-Or & Feierabend 1997). Examination of transgenic tobacco plants with ≈ 10% of wild-type catalase activity has indicated the importance of catalase in maintaining redox balance during salt stress, even under lowintensity light (Willekens et al 1997).…”
Section: Synthesis Of Glycine Betaine and Inositol Derivatives: Linksmentioning
confidence: 99%
“…The steppe regions have very poor vegetation and a very short vegetative period since these conditions limit plant growth (68,138). The high light intensity, high temperature and the temperature difference between night and day increases the generation of reactive oxygen species and thus the risk of oxidative damage.…”
Section: Dong and Chinmentioning
confidence: 99%
“…The high light intensity, high temperature and the temperature difference between night and day increases the generation of reactive oxygen species and thus the risk of oxidative damage. The plants may have developed two strategies to adapt to these severe conditions: antioxidant protection and avoidance from oxidative stress (68). The damage from the electron transfer system results in the formation of free radicals (singlet oxygen, superoxide radical and hydroxyl radicals).…”
Section: Dong and Chinmentioning
confidence: 99%
See 1 more Smart Citation